Análisis del polimorfismo del gen APOE en la población de Barranquilla, Colombia (2023)
Introduction: The genetic variability present in the APOE gene polymorphism is considered an important factor associated with predisposition to diseases affecting lipid metabolism, as well as heart diseases and Alzheimer's disease, among others. Understanding it as a risk factor in different populations and ethnic groups is a useful tool. Objective: To analyze the APOE gene polymorphism and determine allelic and genotypic frequencies of a representative sample of population from Barranquilla, Colombia. Materials and methods: We performed a descriptive and comparative study. The sample size was 227 unrelated individuals from Barranquilla, Colombia Results: The most frequent allele was the e3, with 85%, followed by the e4 allele (13%) and e2 (1.8%). The genotypes found were: e3/e3: 71.8%, e3/e4: 24.2%, e2/e3: 2.2%, e2/e4: 1.3% and e4/e4: 0.4%. The e2/e2 genotype was not found in this study. The sample exhibited the Hardy-Weinberg equilibrium. Conclusion: The frequency of the e3 allele and the e3/e3 genotype was similar to that reported in the literature in countries like Brazil, Mexico, Colombia, and in some Colombian Amerindian ethnic groups. The e2/e2 genotype was absent. This result is consistent with those found in other population groups worldwide. The frequency of the e4 allele and the genotypes associated in this population could be related to the presence of diseases such as hypercholesterolemia, myocardial infarction and Alzheimer.